Interactions with Valuescapes: applications of extra-sensory values in everyday coffee personalization - Miles, Oliver (2025)
Personalization of consumables is increasingly grounded on extra-sensory as well as sensory qualities. Using the everyday example of coffee, this thesis addresses the challenge of creating a values-orientated personalization paradigm that maintains the descriptive and predictive capabilities of sensory product-preference alignment seen in mass market approaches, while also eliciting the extra-sensory qualities more likely evaluated by the consumer end-user as ‘personal’. This paradigm is referred to as the ‘Valuescape’; a theoretical, structural conception of the socio-technical world in which values themselves become objects for interaction.